중장년층의 경력전환역량으로서 진로인식 및 직무지식에 대한 탐색: 교육수요와의 관계를 중심으로 - 이정우(Jungwoo Lee); 김진희(Jinhee Kim); 강충서(Chungseo Kang) (평생학습사회, 2024)
이 연구는 중장년층이 인식한 경력전환역량으로서 진로인식 및 직무지식 수준과 해당 역량 함양을 위한 교육수요 간의 관계를 분석하였다. 중장년에 해당하는 40대와 50대 1,000명을 대상으로 조사 한 자료를 2차항 회귀모형(quadratic regression model)을 통해 분석했다. 분석 결과, 첫째, 중장년층이 인식한 진로인식과 직무지식 수준은 보통 이상으로 나타났으며,두 역량에 대한 교육수요 또한 평균 수준보다 높게 나타났다. 둘째, 진로인식과 교육수요 간에는 독특한 패턴이 나타났는데, 진로인식 수준이 보통일 때는 교육수요가 비교적 낮았으나, 진로인식 수준이 낮거나 매우 높은경우에는 교육수요가 증가하는 경향을 보였다. 셋째, 직무지식과 교육수요간에도 비슷한 경향이 나타났으며, 특히 자신의 직무지식을 낮거나 높게평가하는 중장년층에서 관련 교육에 대한 수요가 상대적으로 높은 경향이나타났다. 이러한 분석 결과를 토대로 향후 중장년층 경력전환을 지원하는교육이 성인학습자의 다양한 수요를 반영하고 고도화 되어야 한다는 점을논의하였다. This study investigates the relationship between perceived career transitioncompetencies—specifically career awareness and job knowledge—and theeducational demand aimed at enhancing these competencies among middle-agedadults. Using data from 1,000 individuals in their 40s and 50s, a quadraticregression model was applied to examine the nonlinear relationship betweencompetency levels and educational demand. Participants generally rated their careerawareness and job knowledge as being above average, with a correspondinglyhigh educational demand targeting these areas. A distinct pattern emerged. Individuals with low or very high levels of career awareness and job knowledgedemonstrated increased educational demand, while those with moderate levelsshowed relatively lower demand. The implications based on these findings werediscussed. KCI Citation Count: 1